An overview: Applications of thermal energy storage using phase change materials. (2020) - Ali, Shahid; Deshmukh, S.P.
Abstract: The energy storage is the capture of energy at one time to utilize the same for another time. This review article deals with thermal energy storing methods and its application in the vicinity of solar water heating systems as well as solar air heating system, solar cooker, green house building, cold storage, refrigeration and air conditioning, solar thermal power plant, defence applications, and the materials used to store that thermal energy effectively. There are large numbers of phase change materials which are used to trap the useful thermal energy to utilize in future for minutes, hours, days, months or even years. This paper provides the information of desirable and undesirable properties of different PCMs.